How Charismatic Leadership, Division of Labor, and Organizational Culture Shape Teachers Performance in Pesantren Kulon Banon - Nashih, Ahmad Fathi; Indaryani, Mamik; Edris, Mochammad (Santri: Journal of Pesantren and Fiqh Sosial, 2024)
This study aims to analyze the influence of charismatic leadership style, division of labor, and organizational culture on teachers’ performance at Pesantren Kulon Banon. Respondents totaled 150 people. The sampling technique in this study used purposive sampling; the respondents were teachers who taught at the Pesantren Kulon Banon, and as many as 150 respondents were taken randomly with a lottery model. The analysis technique used is SEM (Structural Equation Modeling) AMOS. The results of this study indicate that 1) Charismatic leadership style has a positive and significant effect on teacher performance, 2) Division of labor has a positive and significant effect on teacher performance, and 3) Organizational culture has a positive and significant effect on teacher performance.